Quality of match for statistical matches using the American Time Use Survey 2013, the Survey of Consumer Finances 2013, and the Annual Social and Economic Supplement 2014 - Fernando Rios-Avila (Levy Economics Institute of Bard College, 2018)
This paper describes the quality of the statistical matching between the March 2014 supplement to the Current Population Survey (CPS) and the 2013 American Time Use Survey (ATUS) and Survey of Consumer Finances (SCF), which are used as the basis for the 2013 Levy Institute Measure of Economic Well-Being (LIMEW) estimates for the United States. In the first part of the paper, the alignment of the datasets is examined. In the second, various aspects of the match quality are described. The results indicate that the matches are of high quality, with some indication of bias in specific cases.
Keywords: C14; C40; D31; 330; Statistical Matching; American Time Use Survey; Survey of Consumer Finances; Levy Institute Measure of Economic Well-Being (LIMEW); United States